Absurdity in Amar Putra’s of Old Man of Kusumpur - Prayogo Hadi Sulistio; Zuriyati Zuriyati; Saifur Rohman (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This study was aimed at investigating presentation of absurdity in Amar Putra’s of Old Man of Kusumpur. This study analyzed a short story using library research. Researchers used Camus’ idea of absurdity to analyze the main character and other minor characters. In analyzing the data, researchers follow some steps, as follow: 1) read the short story; 2) identify the main character and minor characters; 3) relate the situation and condition faced by the characters with the concept of absurdity; 4) draw conclusion regarding the absurdity in the short story. The finding shows that the main character defines the meaning of life by looking for help from other character in this case a Godlike character named Big Man. The characters in the story choose not to surrender so that they try to seek for help from others. Even though, Fakirchand found the Big Man has already been death due to big flood as natural disaster swept majority of the village where Big Man lived.